2014
DOI: 10.1016/j.neures.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal subtype specification in establishing mammalian neocortical circuits

Abstract: The functional integrity of the neocortical circuit relies on the precise production of diverse neuron populations and their assembly during development. In recent years, extensive progress has been made in the understanding of the mechanisms that control differentiation of each neuronal type within the neocortex. In this review, we address how the elaborate neocortical cytoarchitecture is established from a simple neuroepithelium based on recent studies examining the spatiotemporal mechanisms of neuronal subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 194 publications
(237 reference statements)
2
13
0
Order By: Relevance
“…The PP is then invaded by glutamatergic excitatory projection (pyramidal) neurons to form the cortical plate (CP). They constitute the majority of neurons in the cerebral cortex and are produced at the VZ [ 19 , 20 ]. The first wave of future CP neurons migrates into and splits the PP to create an outer marginal zone (MZ), mostly populated by Cajal–Retzius cells, and an inner, transient subplate.…”
Section: Neuronal Migration Phenotype Of the Reeler Mutant Mousementioning
confidence: 99%
“…The PP is then invaded by glutamatergic excitatory projection (pyramidal) neurons to form the cortical plate (CP). They constitute the majority of neurons in the cerebral cortex and are produced at the VZ [ 19 , 20 ]. The first wave of future CP neurons migrates into and splits the PP to create an outer marginal zone (MZ), mostly populated by Cajal–Retzius cells, and an inner, transient subplate.…”
Section: Neuronal Migration Phenotype Of the Reeler Mutant Mousementioning
confidence: 99%
“…A, arcopallium (chicken); ac, anterior commissure; ADVR, anterior dorsal ventricular ridge (lizard); APH, parahippocampal area (chicken); APHcl, caudolateral APH; APHi, intermediate APH; APHl, lateral APH; APHm, medial APH; APHr, rostral APH; BC, basal complex of the pallial amygdala; CA, Ammon's horns or fields (hippocampus proper; it includes three subfields, but only two are represented here: CA1 and CA3); CDL, dorsolateral corticoid area (chicken; same as APHcl); DC, dorsal cortex (lizard; it contains three subdivisions: medial or DC1, intermediate or DC2, and lateral or DC3); DC2l, lateral part of DC2; DC2m, medial part of DC2; DCM, dorsomedial cortex (lizard; comparable to CA3); DG, dentate gyrus (this includes the MC in lizard and the Hi1 sector of the V-shaped area plus the ventral Hi -also named DG primordium -of chicken); DLP, dorsolateral pallium (chicken; sometimes called temporo-parieto-occipital area); DP, dorsal pallium; H, hyperpallium (chicken dorsal pallium); Hi1, hippocampal field 1 (chicken; it is a ventral part of the V-shaped area, included in the DG); Hi2, hippocampal field 2 (chicken; it is a dorsal part of the V-shaped area, comparable to CA3); Hy, hypothalamus; LC, lateral cortex (lizard; it contains a dorsal part or LCd, which belongs to the Lcs-radial unit and a ventral part or LCv); Lcs, lateral cortical superposition (lizard; it is a radial unit with a double cortical plate: an outer plate formed by LCd and an inner plate formed by DC3; it seems comparable to LEC); LCv, ventral part of LC; LP, lateral pallium; M, mesopallium (chicken lateral pallium); MC, medial cortex (lizard; comparable to DG); Me, medial amygdala; N, nidopallium; NCx, neocortex; NS, nucleus sphericus (lizard); PDVR, posterior dorsal ventricular ridge (lizard); Pir, piriform or olfactory cortex; PO, preoptic area; rp, roof plate; Se, septum; Sp, subpallium; St, striatum; v, ventricle; VLP, ventrolateral caudal pallium; VP, ventral pallium. tricular zone (VZ) of the medial pallial sector is thus defined by strong combinatorial expression of all TFs from early developmental stages [Emx1/2 and Lhx2 from E9.5 or before: Kumamoto and Hanashima, 2014; Lef1 from at least E11.5], and subrogation of either roof plate/cortical hem signals or some of the genes normally induced in the medial pallium (Emx1/2, Lef1, and/or Lhx2) leads to severe malformation of the pallium, involving total or partial agenesis of the HF [Pellegrini et al, 1996;Porter et al, 1997;Galceran et al, 2000;Lee et al, 2000;Tole et al, 2000;Bulchand et al, 2001;Monuki et al, 2001;Machon et al, 2007]. The expression of these genes supports that the indusium griseum (the rostral hippocampal extension) is also a medial pallial derivative [Abellán et al, 2014], although it is unknown whether this structure is affected by the mutations.…”
Section: Genes Involved In Mouse Hippocampal Developmentmentioning
confidence: 99%
“…A previous comparative study showed that the CH is rudimentary in lizards, developed in mice, and highly differentiated in humans . It is well known that the reptilian cortex and the avian dorsal pallium have fewer Reln‐positive cells than mammalian cortices . An increase in the size of the medial telencephalon, including the CH, seems to correspond to the number of CR cells expressing Reln, which might lead to the development of a mammalian‐type enlarged cortex.…”
Section: Discussionmentioning
confidence: 96%